2015
DOI: 10.1371/journal.pone.0139460
|View full text |Cite
|
Sign up to set email alerts
|

How Can Childbirth Care for the Rural Poor Be Improved? A Contribution from Spatial Modelling in Rural Tanzania

Abstract: IntroductionMaternal and perinatal mortality remain a challenge in resource-limited countries, particularly among the rural poor. To save lives at birth health facility delivery is recommended. However, increasing coverage of institutional deliveries may not translate into mortality reduction if shortage of qualified staff and lack of enabling working conditions affect quality of services. In Tanzania childbirth care is available in all facilities; yet maternal and newborn mortality are high. The study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…For Tanzania, some studies suggest that policies aiming to reduce distance or travel time, by expanding service provision, deteriorate service quality when scarce resources are diluted. This may put the poorest people who cannot pay the cost of bypassing their nearest facility at higher risk of receiving suboptimal care [54,55]. To ensure access to adequate care for all, concerted effort and innovative targeting are required.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Tanzania, some studies suggest that policies aiming to reduce distance or travel time, by expanding service provision, deteriorate service quality when scarce resources are diluted. This may put the poorest people who cannot pay the cost of bypassing their nearest facility at higher risk of receiving suboptimal care [54,55]. To ensure access to adequate care for all, concerted effort and innovative targeting are required.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…In a setting of high facility density and limited resources, it has been shown that concentrating available resources in fewer, but strategically selected, facilities/ sites may promote geographic accessibility for all. In Tanzania and other LMICs, positive outcomes in physical accessibility and quality of care were achieved when interventions were supported by the right tools and approaches [55][56][57][58].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Key features and landmarks are digitized to create shapefiles and vector layers of spatial objects that can then be imported and analysed in major analytical software packages broadly used in epidemiological studies (such as Stata, R, ArcGIS and QGIS). Multiple studies of maternity care determinants set in LMICs have already adopted this approach [ 33 , 58 61 ]. Prioritizing accurate, up to date, and reliable geospatial data availability has been highlighted in expert group meetings [ 62 ], but the compilation of geospatial data of health facility census and other ancillary data (e.g., road network) remains a challenge for local teams.…”
Section: Discussionmentioning
confidence: 99%
“…Strong effective managers and supportive supervision may be a key factor in quality health care in resource-poor settings with overwhelmed staff [ 65 , 66 ]. Emerging evidence from the Tanzanian context suggests that concentrating skilled staff in fewer front line facilities, with higher-volume case management, could improve care at birth, and cause minimal loss of population coverage in rural areas [ 67 , 68 ]. As poor rural women bypass facilities (and cross administrative boundaries) with inadequate care at birth provision [ 50 , 69 , 70 ], such a solution may be most pragmatic where skilled health workers are in critical shortage.…”
Section: Discussionmentioning
confidence: 99%